The potential role of nitrate, a nitric oxide donor, in the prevention and treatment of diabetic osteoporosis - Jeddi, Sajad; Kashfi, Khosrow; Ghasemi, Asghar (Frontiers in Endocrinology, 2025)
Approximately 28% of individuals with diabetes have osteoporosis. Diabetoporosis, which refers to the diabetes-related decrease in bone quality and quantity, increases the risk of osteoporotic fractures by 600-700% in individuals with type 1 diabetes (T1D) and by 38-70% in those with type 2 diabetes (T2D) compared to non-diabetic individuals. Decreased nitric oxide (NO) bioavailability contributes to diabetoporosis. This review summarizes the potential role of nitrate as a NO donor in preventing and treating diabetic osteoporosis. Evidence suggests that organic and inorganic nitrates have anti-osteoporotic effects in animal models of osteoporosis, as demonstrated by increasing bone mineral density (BMD, 3-42%) and bone weight (6-160%). Observational human studies indicate a lower fracture risk (6-17%) and a higher BMD (3-5%) following organic nitrate administration. Similar protective effects (7-74% reduction in fracture risk and 8-84% increase in BMD) have been observed with nitrate-rich diets. Randomized controlled trials have also shown that nitrate increases circulating bone formation markers; however, no effect on fracture risk has been reported, and increased BMD (8.8%) was reported only in one study. Nitrate converts to nitrite and then to NO (exogenous NO), increasing NO bioavailability in bone. In addition, nitrate increases the expression of endothelial NO synthase (eNOS), thereby increasing the endogenous NO in bone. Nitrate-derived NO promotes bone formation and reduces bone resorption via the NO/cyclic guanosine monophosphate (cGMP)/protein kinase G (PKG) signaling pathway. In addition to increasing NO availability, nitrate may enhance plasma insulin levels, reduce hyperglycemia, and improve insulin resistance in diabetes, further contributing to nitrates’ anti-osteoporotic effects in diabetic bone. In conclusion, NO-based interventions such as nitrate may have a potential role in preventing and treating diabetoporosis.